2021
DOI: 10.1038/s41523-021-00247-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced breast MRI features correlate with invasive breast cancer angiogenesis

Abstract: Angiogenesis is a critical component of breast cancer development, and identification of imaging-based angiogenesis assays has prognostic and treatment implications. We evaluated the association of semi-quantitative kinetic and radiomic breast cancer features on dynamic contrast-enhanced (DCE)-MRI with microvessel density (MVD), a marker for angiogenesis. Invasive breast cancer kinetic features (initial peak percent enhancement [PE], signal enhancement ratio [SER], functional tumor volume [FTV], and washout fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 58 publications
(25 reference statements)
2
25
0
Order By: Relevance
“…Breast cancer has many clinically approved mAb-based therapies, including trastuzumab, pertuzumab, margetuximab-cmkb, ado-trastuzumab emtansine, fam-trastuzumab deruxtecan-nxki, and sacituzumab govitecan. Serendipitously, DCE-MRI is often used in patients with breast cancer to evaluate tumor development and facilitate treatment planning [ 47 , 48 , 49 ]. Comparable to the method used by Lu et al, patients eligible for tumor resection through surgery that also undergo DCE-MRI can be administered mAb prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer has many clinically approved mAb-based therapies, including trastuzumab, pertuzumab, margetuximab-cmkb, ado-trastuzumab emtansine, fam-trastuzumab deruxtecan-nxki, and sacituzumab govitecan. Serendipitously, DCE-MRI is often used in patients with breast cancer to evaluate tumor development and facilitate treatment planning [ 47 , 48 , 49 ]. Comparable to the method used by Lu et al, patients eligible for tumor resection through surgery that also undergo DCE-MRI can be administered mAb prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic features could also reflect the angiogenesis status and microvascular density in bladder urothelial carcinoma and in clear-cell renal-cell carcinoma [ 42 , 43 ]. Radiomic parameters also predict microvascular density and angiogenesis in breast cancer [ 44 , 45 , 46 ]. In the study by Dooman Arefan and collaborators, a set of radiomic features identified the heterogeneity of tumor microenvironment cells, with an abundance of fibroblasts and the presence of endothelial and immune cells [ 44 ].…”
Section: Liver Premetastatic Niche Formation In Crc Patientsmentioning
confidence: 99%
“…Reasonably, the different phases of metastatic niche formation (each one represented by a puzzle piece in the figure) could be detected by radiogenomics approaches in the near future. The references included in the figure show related manuscript with information about tumor cell extravasation [ 34 , 35 ], neoangiogenesis [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], immunosurveillance evasion [ 44 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] and tumor growth [ 41 ] that could be theoretically translated to metastatic niche detection. Created with BioRender.com.…”
Section: Figurementioning
confidence: 99%
“…DCE-MRI utilizes timed pre-and post-contrast imaging; consequently, the semi-quantitative dynamics of contrast uptake and intensity (initial peak enhancements, delayed phasewashout) are routinely used for radiologic evaluation of DCE-MRI (18). DCE-MRI has proven to be highly sensitive and has revolutionized early detection of breast cancers, particularly in women who are at increased risk for breast cancer (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Consequently, breast DCE-MRI has become standard of care and made it possible to obtain a high-resolution image of breast cancers and their associated vasculature.…”
Section: Breast Dce-mrimentioning
confidence: 99%
“…DCE-MRI is standard-of-care for high-risk cancer screening and surgical staging and is not readily replaced. Furthermore, DCE-MRI time-sequence imaging data provides an opportunity to perform kinetic and pharmacokinetic modeling; this modeling holds promise to better characterize tumors (28,30,39,40), monitor treatment effects (25,31,41), and plan radiation and surgical interventions (29,(42)(43)(44). Given the importance of DCE-MRI imaging, recent efforts have focused on detecting blood vessels in DCE-MRI images.…”
Section: Importance and Limitations Of Mri-based Vessel Detection In Breast Tissue And Cancermentioning
confidence: 99%